STRUKTUR KOMUNITAS MAKROZOOBENTOS SAWAH DI DESA RAJO DANI KECAMATAN PADANG GANTING KABUPATEN TANAH DATAR - Riana, Restia; Nurhadi, Nurhadi; Safitri, Elza (STKIP PGRI Sumbar, 2013)
ABSTRACT An irrigated rice field is a culture system plants that specific viewed a place for growing rice plants, soil preparing, water, and the effect a circle by pesticide gas along with fertilizer. A place research to experience alternation function such as agriculture especially rice plant and freshwater fish protection, this varying condition to cause substratum structure because as base organism waters in general bentos possess habitat immovable relative to affect composition or abudance, because of it already carried out researching The Structure of Macrozoobenthos Community an irrigated rice field at Rajo Dani village sub district office Padang Ganting district of Tanah Datar. The purpose of this study was to determine the macrozoobenthos community structure including water factor physics chemistry while freshwater fish protection. The research already carried out in March 2013 an irrigated rice field at Rajo Dani village. That method used purposive sampling to determine observation three station and three repetition. Removed sample by Fish Net and Identified Zoology Laboratory STKIP PGRI West Sumatera. That result found three class namely Gastropoda, Insecta, Pelecypoda consisting of Lymnaea, Pomacea, Pachydrobiella, Goniobasis, Pleurocera, Melanoides, Thiara, Viviparus, Macromia, Corbicula. Macrozoobenthos abudance to revolve between 186,60-360,00 ind/m2 by means of highest density Pomacea genus as big as 80 ind/m2 at III station althought Macromia and Thiara genus lowest as big as 6,6 ind/m2 at I dan II station. A diversity index of 1,9121-2,1093. A similarity index of 88,89%-100%. This water factor physics chemistry while freshwater fish protection that is Temperature of 28,5-29,5ºC, pH of 7,1-8,0, and Dyxolved Oxygen of 4,99-6,16 mg/l including bottom paddy rice field substratum being muddy loam soil generally. The Structure of Macrozoobenthos Community an irrigated rice field shown by means of composition or abudance lowest that genus according to criteria diversity index from everystation.